Perception of patients included in clinical trials regarding the informed consent process - de Fátima Rodrigues Francisco , Maria (2012)
Clinical trials are the source for the development of new treatment strategies. Informed consent is an ethical safeguard for clinical trials candidates, in that it recognizes the autonomy to make decisions and the right to adequate information. However you must ensure that the information transmitted is properly perceived therefore should be considered variables like age, education and health status to the extent that influence the perception of informed consent process. Other factors seem to influence the perception of informed consent, such as structure and language used on forms, other materials, surroundings, time given for the decision-making and trust between researchers - a physician and subject - patient. It is essential that health professionals introduce strategies of information and communication that promote understanding in the elderly, illiterate and patients from ethnic minorities. It is vital to consider the above factors and understand the motivations, expectations and barriers regarding patient participation in clinical trials. This article provides a broad review of the informed consent process.